Actividad antioxidante y contenido de fenoles totales en vinos sueltos procedentes de Cascas - Reyes Penas, Fiorella (2017)
The objective of this research was to determine antioxidant capacity and total phenol content in five samples of wines from the wineries: Vinos Don Manuelito, Vinos AR, Vinos Lavalet, Wines El Pedregal and Wines Danielito, coming from Cascas. The content of total phenols was made by spectrophotometry at a wavelength of 700 nm using the adapted Folin Ciocalteau method, the wine from the winery Vinos Manuelito being the one with the highest percentage of total phenols expressed as tannic acid 15.02%, unlike wine of the winery "Vinos AR" which presents the lowest percentage 4.82%. The antioxidant capacity expressed as percentage of free radical capture was determined by the method described by Brand-Williams et al, at a wavelength of 720 nm; for each concentration of the ethanolic solution of the samples the percentages of capture of the free radical 2,2-diphenyl-1-picrylhydrazyl (DPPH *) were were obtained. It was observed that the greater the concentration of the sample, the greater the percentage of free radical capture, the wine from the winery Vinos Lavalet having a higher percentage of capture being 96% in its maximum concentration, unlike wine Of the winery Vinos Danielito which was the one that presented the lowest percentage of catch being 83%.